Pola Komunikasi Dokter Terhadap Pasien Dalam Proses Penyembuhan di Klinik LKC Dompet Dhuafa - Fahmi Rusydi; Muhammad Muhammad (STID DI AL-HIKMAH, 2017)
The aim of this study was to determine the pattern of communication in an attempt to give effect cure diseases for patients at the LKC Wallet Dhuafa Clinic. The method used is a qualitative approach. In conclusion, the communication patterns of physicians to the healing process of patients is the psychological approach. Doctors encourage patients to be active, to understand, and is responsible for the healing of individuals. Patterns of communication in this process try, builds, develops, and build relationships both are responsive to social problems being faced.